Effect of square-stepping exercise and basic exercises on functional fitness of older adults - Teixeira, Camila Vieira Ligo [UNESP]; Gobbi, Sebastião [UNESP]; Pereira, Jessica Rodrigues [UNESP]; Ueno, Deisy Terumi [UNESP]; Shigematsu, Ryosuke; Gobbi, Lilian Teresa Bucken [UNESP] (Wiley, 2013)
Aim: The aging process might reduce functional fitness, including balance, which can increase the risk of falls among older adults. Different types of intervention seem to benefit older adults, therefore the purpose of this study was to analyze the effect of a program using square-stepping exercises (SSE) sequences only on functional fitness in older adults. Furthermore, the possible effects were compared with a basic exercise program. Methods: A total of 86 community-dwelling older adults (aged >60 years) were divided into four groups: one group practised only SSE sequences (n=21), the second group practised basic physical exercises (n=20), the third group practised both SSE sequences and physical exercises (n=25); and the fourth group was the control group, which was evaluated in their functional fitness before and after the 16-week research period. Results: Participants who practised basic physical exercises improved in agility and aerobic endurance, and SSE improved balance tests. Conclusions: SSE and basic exercise, practised together or alone, seem to have a good influence on the functional fitness of older adults. In addition, SSE training seems to be an effective new kind of activity for balance training. Geriatr Gerontol Int 2013; 13: 842-848. © 2012 Japan Geriatrics Society.
Keywords: Age; Balance; Functional fitness; Physical activity